Malignant eccrine spiradenoma with florid squamous differentiation. - Lee, H. H. (Korean Academy of Medical Sciences, 1998)
Malignant eccrine spiradenoma (MES) is an exceedingly rare neoplasm of cutaneous adnexal origin. To date, 31 cases have been documented in the literature. We herein report an additional case of MES that arose in longstanding eccrine spiradenoma (ES). A 54-year-old woman was seen for a bluish nodular mass on the right flank that previously had been stable for 7 to 8 years and had recently increased in size and become tender. The excised mass (2.8 x 2.5 x 2.5 cm) had no attachment to the overlying epidermis. Microscopically, 2 to 3 sharply demarcated lobules were surrounded by a markedly thickened and hyalinized fibrous capsule. Of the lesion removed, approximately 20% of the tumor showed typical histologic features of benign ES. In the remaining malignant areas, the typical configuration of benign counterpart, consisting of peripheral rows of small dark basaloid cells and central layers of large pale cells partially forming lumina, was replaced with a massive solid proliferation of large pale cells showing nuclear pleomorphism, prominent nucleoli, increased mitotic activity (reaching 12/10 HPF) and loss of PAS-positive basement membrane. There were multiple foci of florid squamous differentiation in the malignant portion. Cytokeratin, focally S-100 and EMA were expressed in large pale cells, whereas alpha smooth muscle actin and S-100 were positive in small dark basaloid cells. Focal reactivity of CEA and EMA was found in the central lumina. P53 was not expressed in benign areas, whilst in malignant areas an occasional nuclear reaction was disclosed.